Experiences and actions of part-time firefighters’ family members: a critical incident study - Bengt Fridlund; Carina Elmqvist; Anders Svensson; Emelie Lantz; Bengt Nilsson (BMJ Open)
Objectives The purpose of this study was to describe the experiences and actions of part-time firefighters’ family members in rural areas in Sweden.Design The study had an inductive descriptive design and used the critical incident technique.Setting Rural areas, primarily served by a part-time fire station, across Sweden.Participants The study included 25 participants (21 females and 4 males) with experiences of being a family member of a part-time firefighter. Family members who themselves served as firefighters were excluded.Results Being a part-time firefighter’s family member was described into three main areas of experiences: ‘affecting everyday life’, ‘dealing with uncertainty’ and ‘being in this together’. Actions taken were divided into two main areas: ‘pursuing adaptations’ and ‘alleviating difficulties’.Conclusions Family members of part-time firefighters faced increased responsibility at home, managing personal inconvenience and frustration. They offered emotional support for the firefighter, however, expressing a need for guidance on handling firefighters’ emotions and mental health after call-outs. Despite their crucial role, they often felt unrecognised by the fire and rescue service. Nonetheless, they took pride in their firefighter’s contribution to the community and noted positive impacts on the family.